Teachers’ Readiness on Teaching English in Elementary School through Merdeka Curriculum at Elementary Schools in Lunang South Pesisir - Purbowati, Annisa Tri; Tiarina, Yuli (Universitas Negeri Padang, 2024)
This study aimed to figure out Teachers’ Behavioral and Situational Readiness on teaching English in elementary school. This research used a Qualitative research method with a case study approach. The participants in the study were twelve classroom elementary schools' teachers whose were instructed to teach English, especially in grades one, two, four, and five. The data were collected using semi- structured interviews. The findings showed that The teachers’ behavioral readiness depends on their educational background were not ready to teach English in elementary school because there were no teachers who had English educational background. Moreover depending on their pedagogical skill all the teachers were ready to teach. However, they need more improvement to the content knowledge in teaching English. The teachers’ situational readiness depends on providing facilities and tools are ready to teach English in elementary schools. However, there is only one school which had sufficient library, others schools still do not have sufficient libraries, especially in 3T schools which means are rural, underdeveloped, frontier areas and lack in provide complete books.